Ceiriog - Hughes, John Ceiriog, 1832-1887; Edwards, Owen Morgan, Sir, 1858-1920 (Salt Lake City, UT : Project Gutenberg, 2002)
"Ceiriog" by John Ceiriog Hughes is a collection of lyrical poetry and songs written during the late 19th century. The work reflects the life and sentiments of its author, whose experiences are intertwined with the landscapes and cultural heritage of Wales, showcasing a deep affection for the natural beauty and traditions of his homeland. The opening of this collection provides both a prologue and a glimpse into the poet's background, revealing Hughes' early life in the Berwyn mountains and his journey as a bard deeply influenced by his environment. He expresses a longing for the pastoral existence he left behind and the inspiration derived from his roots. This section lays the groundwork for the poems that follow, displaying themes of nostalgia, love for Wales, and the emotional impact of nature, all framed through the context of the author's life and the traditions of Welsh poetry. The tone suggests a blend of personal experience with a broader national pride, hinting at the exploration of both intimate and universal sentiments in the verses that follow. (This is an automatically generated summary.)
Release date is 2002-10-01
Transcribed from the 1902 Ab Owen edition by David Price
Keywords: Wales -- Poetry; Ballads, Welsh -- Texts